A CONVERSATION ANALYSIS OF CLASSROOM INTERACTION IN AN EYL CLASS BY USING UNO CARD - Ayu Tri Nurjanah; Etika Rachmawati (Journal of English Education Program (JEEP), 2022)
This article aims to determine the principles of conversation analysis contained in conversations between teacher and EYL students during class interactions in an EYL class using UNO cards and to find out how teachers apply the principles of conversation in an EYL class. This research uses descriptive qualitative in the form of conversation analysis. The participants involved in this study were one teacher and four EYL students with the research being conducted in one of the courses in Banjar. Research data were collected using two instruments, namely observation (non-participants observation) and interviews (semi-structured). The research findings were analyzed based on 4 machines of interactional structure practice, namely; (1) turn-taking, (2) sequence organization, (3) turn design, and (4) repair, show that the teacher dominates the conversation during classroom interactions. This makes the teacher the first pair part (FPP) followed by young learners as a second pair part (SPP). The results of the interview revealed that teachers must know every psychology that young learners have in order to know the condition of each student so that students' focus does not leave learning. It is also intended that teachers are able to provide appropriate stimuli and methods for young learners. The researcher concludes that the analyzed conversations between teachers and EYL students are in line with the basic principles of conversation analysis. For further researchers, it is hoped that they will be able to explore more broadly the analysis of conversations that occur in-class interactions.